2012
DOI: 10.1007/s00245-012-9181-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a New Variational Model to Restore Point-Like and Curve-Like Singularities in Imaging

Abstract: The paper is concerned with the analysis of a new variational model to restore point-like and curve-like singularities in biological images. To this aim we investigate the variational properties of a suitable energy which governs these pathologies. Finally in order to realize numerical experiments we minimize, in the discrete setting, a regularized version of this functional by fast descent gradient scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Finally u 0 is a given data and here the restriction p ≥ 2N N +2 is assumed to give sense to the discrepancy term Ω |u − u 0 | 2 dx. In [2], under suitable growth assumptions on the integrands f and g, an existence result was proven. It was also shown that functional (1.1) coincides with the lower semicontinuous envelope, with respect to W 1,p loc (Ω)-weak convergence of the following functional F (u, Ω) := Ω f (∆u)dx + Ω g(∇u)dx…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally u 0 is a given data and here the restriction p ≥ 2N N +2 is assumed to give sense to the discrepancy term Ω |u − u 0 | 2 dx. In [2], under suitable growth assumptions on the integrands f and g, an existence result was proven. It was also shown that functional (1.1) coincides with the lower semicontinuous envelope, with respect to W 1,p loc (Ω)-weak convergence of the following functional F (u, Ω) := Ω f (∆u)dx + Ω g(∇u)dx…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper (see [2]) the authors have introduced a new functional of calculus of variations to preserve point-like and curve-like singularities in biological images corrupted by noise. The energy, they deal with, was the following dµ a d|µ a | , dµ 0 d|µ 0 | are the Radon-Nikodym derivatives of the measures µ a and µ 0 with respect to their total variation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations